1996
DOI: 10.1002/abio.370160223
|View full text |Cite
|
Sign up to set email alerts
|

The use of a thermotolerant fermentative Kluyveromyces marxianus IMB3 yeast strain for ethanol production

Abstract: An investigation was carried out on the growth and ethanol production of a novel thermotolerant ethanol-producing Kluyveromyces marxianus IMB3 yeast strain. It grew aerobically on glucose, lactose, cellobiose, xylose and whey permeate and fermented all the above carbon sources to ethanol at 45 OC. This strain was capable of growing under anaerobic chemostat fermentation conditions at 45 OC and a dilution rate of 0.15 h-l and produced I 0 . 9 g / l biomass and 1.8% (v/v) ethanol. An increase in biomass (up to 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0
3

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 26 publications
0
23
0
3
Order By: Relevance
“…Figure 2 shows the growth and ethanol production simultaneously with speciWc growth rate of 0.23 h ¡1 on glucose, whereas on xylose, the cells grew with speciWc growth rate of 0.34 h ¡1 without producing ethanol in aerobic conditions. Banat et al [5] reported speciWc growth rate of Kluyveromyces marxianus IMB3 0.63 and 0.19 h ¡1 on glucose and xylose, respectively, in batch fermentation at 50°C.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Figure 2 shows the growth and ethanol production simultaneously with speciWc growth rate of 0.23 h ¡1 on glucose, whereas on xylose, the cells grew with speciWc growth rate of 0.34 h ¡1 without producing ethanol in aerobic conditions. Banat et al [5] reported speciWc growth rate of Kluyveromyces marxianus IMB3 0.63 and 0.19 h ¡1 on glucose and xylose, respectively, in batch fermentation at 50°C.…”
Section: Resultsmentioning
confidence: 98%
“…The strain has the ability to convert hexose sugars to cell mass as well as ethanol during the growth phase. This ability shows that the yeast follows the Crabtree rather than the Pasteur eVect [5]. The yeast Saccharomyces cerevisiae also follows Crabtree [23].…”
Section: Resultsmentioning
confidence: 99%
“…The production of ethanol by yeast fermentation in tropical countries especially during summer months is not economically viable because of high energy input required to cool the reactors inorder to maintain the temperature during the fermentation process [1]. Thermotolerant yeasts offer potential advantages in alcohol industry by reducing the cost of ethanol distillation saving of energy by avoiding the need to cool reactors and in having faster fermentation rates which makes the process economical [2,3]. Although ethanol is produced by the process of submerged fermentation in various parts of the world, there is tremendous scope for Solid Substrate Fermentation (SSF) because of the following potential advantages [4±6]: (a) less requirement of water (especially attractive in summer months when water is scarce), (b) smaller volumes of fermentation mash, (c) less physical energy requirement, (d) less capital investment, (e) less operating costs and lower space requirement, (f) reduced reactor volumes, easier product recovery less liquid waste to be disposed of and hence less pollution problems.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12][13] Recently, increasing attention has been directed toward developing microbial catalysts for ethanol production at elevated temperatures. [14][15][16][17][18] Fermentation processes conducted at elevated temperatures will significantly reduce cooling costs, improve efficiency of simultaneous saccharification and fermentation, allow continuous ethanol removal by evaporation under reduced pressure, and reduce risk of contamination, all of which would improve profitability of fuel ethanol production from biomass. 15,16,18,19 The temperatures suitable for conventional strains of S. cerevisiae are relatively low (25 to 30 °C), although some S. cerevisiae strains have been isolated that are able to produce ethanol efficiently at 40 °C or 42 °C.…”
mentioning
confidence: 99%